Pengaruh Akuntabilitas, Etika Profesi, dan Pengalaman Auditor terhadap Kualitas Audit pada Lembaga Badan Pemeriksa Keuangan (BPK) RI - Monica Andesti; Khadijah Khadijah; Nur Isra Laili; Maya Richmayati; Ita Mustika (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study is oriented to examine the correlation between Accountability Influence, Professional Ethics, and Auditor Experience on Audit Quality at the Audit Board of the Republic of Indonesia (BPK RI). The research population comprises auditors assigned to the Inspectorate of Batam City. The sample was obtained using a saturated sampling or census method, yielding 33 respondents as representatives of the population. The selection of the entire population as the sample is predicated on the relatively constrained population size, thereby enabling the researcher to evaluate the degree of influence of each variable on the enhancement of audit quality with precision. The research approach employed is quantitative for data acquisition. This type of study, recognized as explanatory research, aims to delineate the extent to which the independent variables affect the dependent variable. The data analytic methodology employed encompassed descriptive analysis of variables, validity and reliability testing of instruments, classical assumption examinations, multiple linear regression, hypothesis testing, model feasibility assessment, coefficient of determination analysis, and t-tests executed via SPSS version 29. The empirical findings revealed that accountability, professional ethics, and auditor experience exert a positive and statistically significant influence on audit quality.